Effects of polymorphisms in the MTHFR gene on 5-FU hematological toxicity and efficacy in Thai colorectal cancer patients - Atasilp, Chalirmporn; Lenavat, Rinradee; Vanwong, Natchaya; Chansriwong, Phichai; Sirachainan, Ekaphop; Reungwetwattana, Thanyanan; Jinda, Pimonpan; Aiempradit, Somthawin; Sirilerttrakul, Suwannee; Chamnanphon, Monpat; Puangpetch, Apichaya; Sankuntaw, Nipaporn; et al. (Frontiers in Oncology, 2022)
Background: The two common methylenetetrahydrofolate reductase (MTHFR) polymorphisms 677G>A and 1298A>C may have been affecting 5-FU toxicity in cancer patients for decades. Drug efficacy has also been shown by previous studies to be affected. In this study, we investigated the effects of these polymorphisms on 5-FU hematological toxicity and treatment efficacy, to provide enhanced pharmacological treatment for cancer patients. Methods: This is a retrospective study involving 52 Thai colorectal cancer patients who were treated with 5-FU based therapy, using TaqMAN real-time PCR to genotype the MTHFR polymorphisms (677G>A and 1298A>C). The toxicity and response rate were assessed using standardized measures. Results: Neutropenia was significantly more likely to be experienced (P=0.049, OR=7.286, 95% CI=0.697-76.181) by patients with the MTHFR 677G>A polymorphism, in the same way as leukopenia (P =0.036, OR=3.333, 95%CI=2.183-5.090) and thrombocytopenia (P<0.001, OR=3.917, 95%CI=2.404-6.382). The MTHFR 1298A>C polymorphism had no statistical association with hematological toxicity in 5-FU treatment. The response rate to 5-FU was not significantly affected by these two polymorphisms. Conclusion: The MTHFR polymorphism 677G>A is a significant risk factor for developing leukopenia, neutropenia and thrombocytopenia as toxic effects of 5-FU therapy in cancer patients. Therefore, patients receiving 5-FU-based therapy should be aware of their polymorphisms as one risk factor for experiencing severe toxicity.